Study of Cooling System in Internal Combustion Engine Improving Performance with Analyzing the Material Alloy FHT 004 Surface Roughness - A.Z.Zokirjonov; Prof., T.O.Almataev; A.Madrakhimov (Genius Journals, 2023)
Cooling system of the engine is one of main essential systems for automobiles, which maintains the engine temperature to the sustain conditions. Hence the main objective of this project work is to propose a study case on production of Auto Climate Control LLC radiator T-250 and its material Alloy FHT 004 which is used for water tube as a part of radiator. Main purpose of this article is clarifying the negative impacts of newlyproduced radiators and study case on material surface roughness.
Keywords: Automobiles; Internal Combustion System; Radiator